Candidate loci for leaf angle in maize revealed by a combination of genome-wide association study and meta-analysis - Duan, Haiyang; Li, Jianxin; Sun, Yan; Xiong, Xuehang; Sun, Li; Li, Wenlong; Gao, Jionghao; Li, Na; Zhang, Junli; Cui, Jiangkuan; Fu, Zhiyuan; Zhang, Xuehai; et al. (Frontiers in Genetics, 2022)
Leaf angle (LA) is a key component of maize plant architecture that can simultaneously govern planting density and improve final yield. However, the genetic mechanisms underlying LA have not been fully addressed. To broaden our understanding of its genetic basis, we scored three LA-related traits on upper, middle, and low leaves of 492 maize inbred lines in five environments. Phenotypic data revealed that the three LA-related traits were normally distributed, and significant variation was observed among environments and genotypes. A Genome-Wide Association Study (GWAS) was then performed to dissect the genetic factors that control natural variation in maize LA. In total, 85 significant SNPs (involving 32 non-redundant QTLs) were detected (P ≤ 2.04 × 10−6), and individual QTLs explained 4.80%–24.09% of the phenotypic variation. Five co-located QTLs were detected in at least two environments, and two QTLs were co-located with multiple LA-related traits. Forty-seven meta-QTLs were identified based on meta-analysis combing 294 LA-related QTLs extracted from 18 previously published studies, 816 genes were identified within these meta-QTLs, and seven co-located QTLs were jointly identified by both GWAS and meta-analysis. ZmULA1 was located in one of the co-located QTLs, qLA7, and its haplotypes, hap1 and hap2, differed significantly in LA-related traits. Interestingly, the temperate materials with hap2 had smallest LA. Finally, we also performed haplotype analysis using the reported genes that regulate LA, and identified a lot of maize germplasms that aggregated favorable haplotypes. These results will be helpful for elucidating the genetic basis of LA and breeding new maize varieties with ideal plant architecture.